The role of trauma in deterrence strategy engagement. Issue 3 (19th May 2018) - Gibson, Sandy; Lombardozzi, Jillian
ABSTRACT: Pulling-levers deterrence strategies work to reduce firearm violence through engaging known violent offenders. As having a history of personal trauma contributes to increased firearm violence, a better understanding of the role of trauma can help to strategically develop engagement strategies. This study uses baseline data from Trenton Violence Reduction Strategy (TVRS) to explore differences among those who chose to engage in TVRS and those who did not after receiving the deterrence messaging. Results show no difference in overall LSC-R score between those who did and did not engage, although there are clear nonsignificant differences with specific types of trauma.